Analysis of Consumptive Behavior Using Shopee and Implications of Islamic Values - Harahap, Alya Rahmayani; Muniruddin, Muniruddin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The study aims to analyze the impact of the e-commerce application (Shopee) on the consumption behavior of the Bukit Martajam Village community, and to investigate this behavior from an Islamic perspective. The study employs a quantitative methodology, utilizing probability sampling and random sampling techniques, with a maximum of 80 participants. We analyzed the data using a simple regression test and SPSS 25 Statistics. The results showed that the use of Shopee has a significant influence on people's consumptive behavior, with a significance value (0.018) < 0.05 and a t-count value (2.413) > t-table (1.663). These findings indicate that the use of Shopee has an impact on consumptive behavior, and it is important to integrate Islamic values in consumption behavior to avoid negative impacts. Intensive use of Shopee tends to increase consumptive behavior in Bukit Martajam Village. In Islam, the principle of kesederhanaan strongly influences consumption behavior. Even so, Shopee makes it simple to fulfill needs. This study's implications suggest that we should teach Islamic values about wise consumption, encouraging people to avoid excessive consumption and strengthening their understanding of balance in daily life to reduce negative impacts like materialism and wastefulness.